Microfabricated Ion‐Selective Transistors with Fast and Super‐Nernstian Response. Issue 48 (29th October 2020) - Han, Sanggil; Yamamoto, Shunsuke; Polyravas, Anastasios G.; Malliaras, George G.
Abstract: Transistor‐based ion sensors have evolved significantly, but the best‐performing ones rely on a liquid electrolyte as an internal ion reservoir between the ion‐selective membrane and the channel. This liquid reservoir makes sensor miniaturization difficult and leads to devices that are bulky and have limited mechanical flexibility, which is holding back the development of high‐performance wearable/implantable ion sensors. This work demonstrates microfabricated ion‐selective organic electrochemical transistors (OECTs) with a transconductance of 4 mS, in which a thin polyelectrolyte film with mobile sodium ions replaces the liquid reservoir. These devices are capable of selective detection of various ions with a fast response time (≈1 s), a super‐Nernstian sensitivity (85 mV dec −1 ), and a high current sensitivity (224 µA dec −1 ), comparing favorably to other ion sensors based on traditional and emerging materials. Furthermore, the ion‐selective OECTs are stable with highly reproducible sensitivity even after 5 months. These characteristics pave the way for new applications in implantable and wearable electronics. Abstract : Microfabricated ion‐selective transistors with fast response and super‐Nernstian sensitivity are demonstrated. The remarkable performance arises from the use of a thin polyelectrolyte film as an internal ion reservoir between the ion‐selective membrane and the organic electrochemical transistor. The sensor architecture is generic and applicable to sensing of various ions, opening new frontiers for wearable and implantable ion sensors.